Employment status of patients with schizophrenia spectrum disorder treated with long acting injectable paliperidone palmitate: Real world mirror image study. (1st June 2022) - Markovic, M.
Abstract : Introduction: Schizophrenia spectrum disorders may severely limit ability to achieve and maintain gainful employment of affected working-age individuals. Objectives: Assess the employment status in patients with schizophrenia spectrum disorders treated with long acting injectable paliperidone palmitate after the switch from oral antipsychotics. Methods: A single centre mirror image design study of 115 patients with schizophrenia spectrum disorder was conducted in a tertiary level psychiatric hospital. Data were collected for period of 12 months prior toand 12 months after switching from oral antipsychotic to long acting injectable paliperidone.Employment status for 6 enrolled patients was missing. Results: Mean age of enrolled patients was 38, 4±11, 6 years. Of the 109 patients analyzed for employment status, 44, 4% remained employed for 12 months after switching to long acting injectable paliperidone while 4, 6% patients changed their employment status from unemployed to employed after the switch. No patient changed their employment status from employed to unemployed after the switch. 9, 2% patients were already retired at the beginning of study period and 5, 5% of patients maintained their student status. 36, 7% patients remained unemployed for the whole study period. The correlation between employment status of employed and unemployed patients and duration of illness was borderline significant with p=0, 049. Conclusions: The data from this study suggest that use of long acting injectable paliperidone contributed to preservation of working ability of working-age patients suffering from schizophrenia spectrum disorders. Disclosure: No significant relationships.